Assessing the Impact of Road and Land Use on Species Diversity of Trees, Shrubs, Herbs and Grasses in the Mountain Landscape in Southern Africa - Lisboa, Sá Nogueira; Domingos, Francisco; Vallius, Elisa; Lensu, Anssi; Macamo, Ernesto; Sitoe, Almeida (Frontiers in Conservation Science, 2022)
Land-use changes are the most important driving force for vegetation change in Southern Africa. Mountain landscape, described as a global biodiversity hotspot due to high endemism, is threatened by land-use change, including management and modification of vegetation. However, the mountain landscape is understudied in terms of the impact of land use on biodiversity compared to Savana woodlands, known as Miombo, in Southern Africa. Therefore, there have been underrepresented globally in understanding how mountain ecosystem is shaped with land-use change. Hence, little is known about how land use affects plant diversity in a mountain landscape. This study was conducted to compare the plant diversity of trees, shrubs, herbaceous, and grasses among Forest, Fallow, Agriculture, and Roads in the Moribane Forest Reserve (MFR), in Eastern Chimanimani Mountain landscape in Mozambique. To assess this, we conducted 45 transects along the roadside and randomly established 24 quadrats in the Agriculture fields and Fallow and 26 quadrats in the pristine Forest. In each transect and quadrats, we recorded the occurrence of four plant life forms (trees, shrubs, herbaceous, and grass species) to determine the alpha and beta-diversity across land-uses, and we assessed the invasiveness of each species. Species composition varied significantly among the land-uses types. Roadside had higher species diversity and highest invasive species (138 total species of all plant life forms; 31 invasive species) following Fallow (81; 20), Forest (78; 19), and Agriculture (72; 31). There was no similarity in species between roads and other land-uses. Furthermore, Road recorded the highest average species turnover for all plant life forms following Agriculture, Forest, and Fallow. Among the plants, the most important life form was herbaceous with 143 species, following grass with 86 species, shrubs with 86, and trees with 65 species. This study has important implications for local environmental authorities, which rely on mostly subjective and partial environmental impact assessments that do not consider the road edge effects. This study is unique in collecting and analysing data on different plant life forms on roadside linked with a range of different land-use types within a small region of a mountain landscape in sub-Saharan Africa.